PENGEMBANGAN MODEL DINAMIKA DAN PROYEKSI EKSPOR INDONESIA KE BEBERAPA NEGARA MITRA DAGANG UTAMA - Mohammad Abdul Mukhyi (Jurnal Universitas Paramadina, 2013)
AbstractThe phenomenon that Indonesia can not continue to rely on foreign exchange earnings from oil and gas sector and labor (workers and migrant workers) due to the multiplier effect that occurs relatively small and too small in creating foreign exchange. Indonesia as an agricultural country rich in natural resources and is not optimal use peluan market potential for development as a major factor of foreign exchange as well as improving the welfare of society in general and farmers in particular. Similarly, in the non-oil sector development is one of the key strategies to spur economic growth in the future, is still considered to have the opportunity to be developed and exported, because Indonesia is actually wealthy and a wide variety of non-oil and gas sectors that has not been used optimally.This research is to develop a modeling approach for non-oil exports (the main export sector) and game theory simulation variable changes affecting non-oil exports to the countries of Indonesia's main export.The main indicators of research output comprises an integrated export projection model with dynamic modeling approach, the results of this study can be used by governments as an input in the formulation of export targets (planning), the formulation of policies to boost exports and anticipatory policy dynamics of Indonesian exports and dynamics of the world economy. The main contribution of the GDP of Indonesia contributed the largest non-oil sector is the manufacturing sector, which is in line with the existing data in the field, which is further supported by the main factors forming the dynamic model is agriculture, industry, and trade and excavation pertambagan, hotels and restaurants. Dynamic models of non-oil exports have accounted for factors affecting internal and external exports of Indonesia, and has been found supporting factors (domestic and foreign investment, inflation, and oil prices).Keywords: export, dynamics models, projections, CGE.